The CD1d-natural killer T cell axis in atherosclerosis - Bondarenko, S.; Catapano, A.; Norata, Giuseppe (2014)
A key role for 'lipid-sensing' CD1-restricted natural killer T (NKT) cells in the pathogenesis of atherosclerosis has been suggested. However, the biology of NKT cells remains poorly characterized, as in different experimental settings their activation was reported to both stimulate and suppress innate and adaptive immune responses. Most of the data from experimental models suggest that NKT cells are proatherogenic; however, it is debated whether the increase in atherosclerosis observed following NKT cell stimulation is a consequence of the inability to induce functional NKT cells rather than the proatherogenic nature of NKT cells. CD1d-expressing antigen-presenting cells and NKT cells were detected in mouse and human atherosclerotic lesions. Furthermore, several lysophospholipids and glycosphingolipids, known to accumulate in atherosclerotic plaques, are antigenic for human NKT cell clones. Lipid transfer proteins, such as apolipoprotein E and microsomal triglyceride transfer protein, are central to NKT cell responses. All these data suggest a profound relation between lipid metabolism, CD1d-NKT cell axis activation and atherosclerosis. In this review, we summarize the advances and gaps in our knowledge of NKT cell biology in the context of atherosclerosis as well as the possibility of influencing NKT cell polarization toward an atheroprotective phenot ype. Copyright © 2013 S. Karger AG, Basel.